THE IMPORTANCE OF WRITING MATERIALS IN THE DEVELOPMENT OF LANGUAGE SKILLS - Ro‘za Sharipova Bobir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The development of language skills is a multifaceted process, and writing materials serve as a critical tool in enhancing these abilities. This article explores the role of writing materials in fostering vocabulary expansion, improving grammar and syntax, and strengthening cognitive and communication skills. It highlights how writing exercises promote creativity, reinforce reading comprehension, and build confidence in language use.